Hubungan Antara Lamanya Bekerja Sebagai Penambang Batu Kapur Dengan Nilai Vo2 Maks Di Pertambangan Daerah Gunungkidul - Widodo, Aris; , Wahyuni, S.Fis., M.Kes (2017)
Background: Working period is a period of time or duration of labor was working somewhere. The longer people work, the greater the risk of occupational disease. Excessive exposure to dust can cause health problems, especially lung health.work as limestone ferryman in Gunungkidul cause decreased of VO2 Max value due to continuous exposure to dust and long periods without the use of personal protective equipment disposable masks Objective: The purpose of this research to know relationship between working periode as limestone ferryman with VO2 max value in mining Gunungkidul area Methods: Type of research is quantitative, to determine the relationship between working periode as limestone ferryman with Vo2 maxs value. Data collection techniques using by test six minute walk test to know Vo2 maxs value and quitionnaires the list of questions that will be used by researchers to obtain data from the source directly through the communication process or by asking questions Results: After processing statistical data using chi square test, there is reliationship between working periode as limestone ferryman with Vo2 maxs value obtained p = 0.036 means that Ha Ho accepted or rejected. Conclusion: There is a relationship between working periode as limestone ferryman with VO2 Max value. Keywords: working periode as limestone ferryman, VO2 Max value